The principle of universality from a legal and effective perspective in ecuadorian social security - Núñez Ávila, María Dolores (2021)
The Constitution of Ecuador recognizes the principles of social security. These principles constitute an evaluation and hermeneutic tool for the different social security systems. In these principles, we find the universality; the principle of universality is an instrument of social equality, and it broke the class scheme in which social security. In Ecuador, since 2008, universal coverage of social security has been extended to unpaid household workers. The man object analyzes the principle of universality from a legal approach, the contributory and non-contributory social security system applied in Ecuador, and the analysis of the functioning of the Ecuadorian Institute of Social Security and the Bank of the Ecuadorian Institute of Social Security. For this, a deductive-inductive conceptual, doctrinal, legal, jurisprudential, and pragmatic analysis has allowed the detection of specific elements limiting access to social security and structural gaps forsaking sectors of the population, specifically those covered by the non-contributory model.